Plan Estratégico de Marketing para Caracterizarla Posición Competitiva de la Empresa de Transportes ITTSA de la Ciudad de Trujillo”. - Diaz Flores, Jhonatan Marlon (2012)
The purpose of this is to develop a Strategic Marketing Plan, in order to identify strategies that can be used by the transport company ITTSA Trujillo City, allowing improve their competitive position. To achieve this purpose, the main studies were: a Strategic Analysis, which in turn became an External Analysis (here performed the analysis of market trends, the behavior of buyers, competitive structure and the analysis of the macro) and Internal Analysis (here situational analysis was performed of the company and competitor analysis priority)._x000D_ We used multivariate techniques such as Principal Components Analysis to identify the profile or users, segmenting them according to their personality traits as their buying habits, and Correspondence Factor Analysis was used to classify transport company’s attributes as perceived by potential consumers._x000D_ On the hand we proceeded to make the Strategic Plan Formulation, with reference to the studies and results obtained on the Strategic Analysis and the FODA Analysis conducted in the company, which formed a basis of information identified optimally marketing strategies to consider in our plan._x000D_ It concluded select three marketing strategies: the strategy of “Concentration” of “Market Penetration” and “Challenger Strategy”, which according to the projection after application, showed an increase in the level of ticket sales for the next five years resulting in improving the company’s competitive position ITTSA, this was confirmed using the Pearson Correlation Coefficient (r=0.9998) which shows the high correlation between sales goals and positioning